Managing digital risk in Malaysian cultural institution / Zuraidah Abd. Manaf and Aliza Ismail. - Abd. Manaf, Zuraidah; Ismail, Aliza (2009)
It is becoming a trend for cultural institutions to digitise their resources. However, they most oftenly overlook the issue of sustainability of their materials that have been digitised. Findings from previous research has revealed that there are many issues involves in the management of digitisation of cultural heritage resources in the country. One of the significant findings is the ability of the institutions to sustain their digitised resources. The paper will discuss issues related to the risk management of digital resources in Malaysian cultural institutions. The objectives of the study is to explore and understand the state of the art of managing digital resources focusing on the availability of risk strategy practice the by cultural institutions in Malaysia in order to maintain and preserve their digitised resources. The study adopt multiple case study approach where three selected cultural institutions participated. The findings of this study contribute towards the dissemination of the new knowledge specifically in the management of digital preservation of cultural resources available in Malaysia.